Rural non- farm employment in India: a focus on food for work - Majumder, Bhaskar (New Delhi, 2007)
Book Summary of Rural Non-Farm Employment In India: A Focus On Food For Work Poverty in India considered predominantly as a rural phenomenon can be tackled not only by raising the level of total rural income but more by redistribution of rising rural income. The focus of this book is on distribution of rural incomes considered as one intricately linked with creation of mandays in productive works and employing rural workers by both the number of persons employed and mandays. Employability of the workers avaialble in India's rural economy maybe linked not only with the skill of the workers but also on the employment generating ability of the productive assets created initially by the workers engaged initially.
Keywords: Employment